The poetics of Claudian : panegyric in the ancient epic tradition - Ware, Catherine Mary (Trinity College (Dublin, Ireland). Department of Classics, 2006)
The purpose of this thesis is to examine Claudian’s political work as epic poetry, written by a poet who specifically associates himself with Homer, Ennius and Vergil, and whose work alludes to the epics of Ovid, Lucan, Valerius Flaccus, Silius Italicus and Statius. Claudian’s reliance on their work and his varied techniques for the incorporation of allusion is essential to the full understanding and appreciation of the poetry. The introduction discusses the prose and verse traditions of panegyric, focusing in particular on the relationship between panegyric and epic, and discussing the importance of the Aeneid in this regard. Vergil’s understanding of contemporary Roman identity and nationhood challenged future epic poets to imitate his achievement. The first section, comprising three chapters, examines Claudian’s poetic technique. Chapter 1 deals with Claudian’s poetic identity, concentrating in particular on the prefaces in which he creates his literary persona, and states his poetic and generic ambition. His epic claim, while insistent, has marked ambiguities: Claudian suggests that the reader must be alert for generic interplay; as will be noted, his reliance on Ovid throughout his work suggests that he follows Ovid’s manipulation of genre.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin